2022
DOI: 10.3389/fped.2022.1015769
|View full text |Cite
|
Sign up to set email alerts
|

Applications of next generation sequencing in the screening and diagnosis of thalassemia: A mini-review

Abstract: Thalassemias are a group of inherited blood disorders that affects 5–7% of the world population. Comprehensive screening strategies are essential for the management and prevention of this disorder. Today, many clinical and research laboratories have widely utilized next-generation sequencing (NGS) technologies to identify diseases, from germline and somatic disorders to infectious diseases. Yet, NGS application in thalassemia is limited and has just recently surfaced due to current demands in seeking alternati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 66 publications
0
8
0
Order By: Relevance
“…NGS among thalassemia carriers is widely used, especially in China, as it helps identify unknown mutations and detect missed thalassemia simultaneously. Following the review by Suhaimi SA et al, a few studies used NGS as part of thalassemia screening [ 28 ]. For example, Shang et al and He et al conducted a survey on population and premarital screening programs and found that 12.1% of the variants were missed when using Hb analysis, an additional 35 couples were at risk, and 27.5% missed the carrier, respectively, based on NGS screening methods [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NGS among thalassemia carriers is widely used, especially in China, as it helps identify unknown mutations and detect missed thalassemia simultaneously. Following the review by Suhaimi SA et al, a few studies used NGS as part of thalassemia screening [ 28 ]. For example, Shang et al and He et al conducted a survey on population and premarital screening programs and found that 12.1% of the variants were missed when using Hb analysis, an additional 35 couples were at risk, and 27.5% missed the carrier, respectively, based on NGS screening methods [ 27 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional PCR methods using targeted primers do not account for the less common or unknown mutations of any given population. NGS, on the other hand, is able to identify unknown, and even novel, mutations that are not picked up by conventional PCR methods [ 28 ]. For that reason, NGS has become increasingly popular for finding the definitive diagnosis and even for the screening of carriers of thalassemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, these approaches have been limited by laborious procedures, lower throughput, and high requirements for laboratory personnel. In recent years, next‐generation sequencing (NGS) has been used for genetic screening and molecular diagnosis of thalassemia patients (He et al., 2017; Suhaimi et al., 2022), because of its incredible capacity to identify rare or novel pathogenic variants. Nevertheless, its time‐consuming nature and the difficulties in interpreting variants of uncertain significance restrain its further utilization in carrier screening.…”
Section: Introductionmentioning
confidence: 99%
“…Next-generation sequencing (NGS), also known as second-generation sequencing (SGS), has found wide application in clinical practice for its ability to identify mutations across the whole human genome, which can reveal various genetic diseases. However, there are several limitations that hinder its application as a stand-alone technology for screening and diagnosing thalassemia, requiring the aid of Gap-PCR and Sanger sequencing ( Figure 1 ) ( 5 ). Third-generation sequencing (TGS) has emerged as an alternative method that demonstrates great potential for thalassemia detection.…”
Section: Introductionmentioning
confidence: 99%
“… The general process flow, advantages and disadvantages for screening and diagnosing thalassemia using conventional, NGS and TGS approaches. Figure adapted from Suhaimi et al ( 5 ). TGS, third-generation sequencing; NGS, next-generation sequencing; FBC, full blood count; PCR, polymerase chain reaction; ARMS, amplification refractory multiple sequencing; HPLC, high-performance liquid chromatography; MLPA, multiplex ligation-dependent probe amplification.…”
Section: Introductionmentioning
confidence: 99%